The Darkness and the Oracle of Trophonius in Lebadea - Gordillo-Hervás, Rocío (ARYS. Antigüedad: Religiones y Sociedades, 2023)
In his Description of Greece, Pausanias gives a detailed account of the workings of the oracle of Trophonius, the hero responsible for the construction of the temple of Apollo at Delphi, which was located in Lebadea (Boeotia). According to Pausanias, before accessing the oracle, visitors had to perform a complex nocturnal ritual that prepared them for contact with the hero. This chapter will analyse the role of darkness in the different stages of the ritual and how it could influence the oracular perception of the consultant. A comparative study will be carried out between the preparation rituals of the oracle’s visitor and Greek funerary rituals. The similarities between the two types of ceremonies suggest that the consultant had to prepare themselves in order to symbolically enter the afterlife and perform the nekya with the hero.